Modernité(s) chez Martha Graham et Doris Humphrey, artistes fondatrices de la danse moderne étatsunienne dans les années 1930 - Claudie Servian (IdeAs)
This article explores the link between the notion of modernity and North-American dance in the 1930’s. By studying the various aspects of this concept through an analysis of selected choreographies by Martha Graham (1894-1991)and Doris Humphrey (1895-1958), the pioneers of modern dance, this paper aims to show how modernity, central to these choreographers’ aesthetics, pervades their work. The notion of modernity in the United States is both complex and highly connoted, thus difficult to define clearly. Its implications are different in Europe and in the United-States. It refers to a return to the past in order to discover a new form of artistic activity. It also reflects contemporary preoccupations.